CESifo World Economic Survey May 2009 - Gernot Nerb; Anna Stangl (CESifo World Economic Survey, 2009)
World Economic Climate: World Economic Climate improves somewhat - Economic Expectations: Economic expectations brighten, while assessments of the current economic situation deteriorate further - Inflation: Further decline of inflation expectations, but no deflation expected - Interest Rates: Further decline of short-term interest rates, and stabilization of long-term interest rates expected - Currencies: US dollar seen as slightly overvalued - Special Topic: Counterfeiting and piracy
Keywords: 330